NDED - Numerical derivatives from equispaced data - Egidi, Nadaniela; Giacomini, Josephin; Maponi, Pierluigi; Youssef, Michael (Journal of Approximation Software, 2024)
Procedure NDED computes the numerical derivatives of order ν from equispaced data. This is based on the iterated application of a spectral algorithm for the computation of the first order derivative. A preliminary test of the procedure gives satisfactory results.